External mechanical perturbations challenge postural stability in dogs - Lutonsky, Christiane; Peham, Christian; Mucha, Marion; Reicher, Bianca; Gaspar, Rita; Tichy, Alexander; Bockstahler, Barbara (Frontiers in Veterinary Science, 2023)
This study aimed to explore the effect of external mechanical perturbations on postural stability (PS) in dogs using the body center of pressure (COP). Thirteen sound adult dogs were included in this study. PS was tested during quiet standing on a pressure measurement plate. The conditions included a standard standing measurement and external mechanical perturbations conducted using six settings on a motorized training platform with different intensities of speed and amplitude. Measurement conditions were compared using linear mixed-effects models, followed by multiple comparisons using Sidak’s alpha correction procedure. Compared with the standing measurement, external mechanical perturbations resulted in a significant increase in almost all COP parameters, indicating a challenge for the PS. Furthermore, an increase in amplitude had a greater effect than an increase in speed, whereas the combination of the highest intensities of amplitude and speed was not well tolerated by the dogs. The mediolateral COP displacement was significantly greater than the craniocaudal COP displacement during standing measurement and conditions with a small amplitude, whereas no significant difference was observed during settings with an increased amplitude. To the best of our knowledge, this is the first study to demonstrate the effects of a balance training device in dogs. Therefore, the intensity of the training programs on motorized platforms or similar devices can be controlled by the wobbling amplitude of the platform.